SIFO 1989: The natural step - Swedish Institute of Public Opinion Research; Det naturliga steget (Swedish Institute of Public Opinion Research, 2025)
This study was carried out by the Swedish Institute of Public Opinion Research (SIFO) at the request of an environmental campaign called ´Det naturliga steget´. The survey was conducted on two occasions: initially prior to the implementation of the campaign “The Natural Step” and subsequently following its conclusion. It included items measuring respondents’ concerns over the past year, their interest in and knowledge of environmental issues, perceived causes of environmental problems, and the degree of concern regarding specific environmental threats. Additional questions assessed levels of trust in various societal actors in relation to environmental matters, as well as individual engagement in environmentally beneficial activities. The post-campaign survey also incorporated questions regarding exposure to the campaign and respondents’ perceptions of its content and impact.

Denna studie genomfördes av SIFO på uppdrag av en miljökampanj kallad ”Det naturliga steget”. Undersökningen genomfördes vid två tillfällen: först före genomförandet av kampanjen ”Det naturliga steget”, och därefter efter att kampanjen avslutats. Den omfattade frågor som mätte respondenternas oro under det senaste året, deras intresse för och kunskaper om miljöfrågor, uppfattade orsaker till miljöproblem samt graden av oro för specifika miljöhot. Ytterligare frågor berörde förtroendet för olika samhällsaktörer i miljörelaterade frågor samt individens egna engagemang i miljöförbättrande åtgärder. I den del av undersökningen som genomfördes efter kampanjen ingick även frågor om i vilken utsträckning man tagit del av kampanjens innehåll samt hur detta uppfattades.
SIFO 1989: Det naturliga steget
Keywords: ENVIRONMENT; MILJÖ; TRUST; FÖRTROENDE; POLLUTANTS; MILJÖFARLIGA ÄMNEN; ENVIRONMENTALISTS; MILJÖAKTIVISTER; WORKING CONDITIONS; ARBETSFÖRHÅLLANDEN; ENVIRONMENT POLICY; MILJÖPOLITIK; ENVIRONMENTAL AWARENESS; MILJÖMEDVETENHET; Information society; Informationssamhället; Environment and conservation; Miljö och naturvård; Social Sciences; Samhällsvetenskap